Effects of Planktonic Food Organisms on Fatty Acid Composition of Penaeus monodon Fabricius Larvae - CHOTIPUNTU, Piyapong (Walailak Journal of Science and Technology (WJST), 2011)
Penaeus monodon larvae at the first mysis stage were reared to the first post larval stage (PL-1) in 1-L lmhoff cones on three different diets: rotifers enriched with Pavlova lutheri (Rp), rotifers enriched with a commercial micro-encapsulated diet (Re), and a mixture of P. lutheri and Artemia salina nauplii (PA). The 14 essential fatty acids in the larvae that received the three different diets were measured and compared. Profiles of the fatty acids in the larvae and diets were also described. Fatty acid composition of the larvae resembled that of the diets. The total fatty acid per dry weight of larvae was higher in larvae fed PA than that of larvae fed Rp or Re (p<0.01). The highest levels of the four major essential fatty acids – 18:2(n-6), 18:3(n-3), 20:5(n-3), and 22:6(n-3) – were found in the larvae that received Re, PA, and Rp respectively. There was no significant difference in survival rates (86.7 - 92.5%) of the larvae receiving different diets (p>0.05). The fatty acid composition of the larvae fed a mixture of Pavlova and Artemia resembled that found in Artemia but not in Pavlova.